The Extent of External Auditing Efficiency in Limiting Creative Accounting Practices "Empirical Study on External Auditing bureau in Misrata" - Shaboun, Abubaker; shwairef, Abdalla; Salem, Abdusalam (Journal of Pure & Applied Sciences, 2021)
After the collapse of large international companies and the emergence of the creative accounting methods, interest has increased in the audit process. For Companies  to achieve its goals efficiently, have to apply auditing which is  considered one of the main pillars of the corporate control system. This study aims to identify the extent of the efficiency of external auditing, and attempts to investigate its effect on creative accounting practices. In addition, the study aims to identify the extent to which the corporate management use creative accounting methods as perceived by  external auditors and academics in the city of Misrata. Therefore, a questionnaire was designed for the purpose of collecting data to measure the study’s variables. The data analyzed using the (SPSS) statistical software program. This study contributed to enriching the theoretical side of the creative auditing and accounting process. The study found that the efficiency of external auditing is moderate, and that there is an existence of creative accounting practices in the companies studied. The finding also, showed that the efficiency of external auditing plays a vital role in limiting creative account accounting practices.